Pseudomonas synxantha volatile organic compounds: efficacy against Cadophora luteo-olivacea and Botrytis cinerea of kiwifruit - Di Francesco, Alessandra; Jabeen, Farwa; Vall-llaura, Núria; Moret, Erica; Martini, Marta; Torres, Rosario; Ermacora, Paolo; Teixidó, Neus (Frontiers in Plant Science, 2024)
Volatile organic compounds (VOCs) are responsible for the antagonistic activity exerted by different biological control agents (BCAs). In this study, VOCs produced by Pseudomonas synxantha strain 117-2b were tested against two kiwifruit fungal postharvest pathogens: Cadophora luteo-olivacea and Botrytis cinerea, through in vitro and in vivo assays. In vitro results demonstrated that P. synxantha 117-2b VOCs inhibit mycelial growth of C. luteo-olivacea and B. cinerea by 56% and 42.8% after 14 and 5 days of exposition, respectively. In vivo assay demonstrated significant inhibitory effects. VOCs used as a biofumigant treatment reduced skin-pitting symptoms disease severity by 28.5% and gray mold incidence by 66.6%, with respect to the untreated control. BCA volatiles were analyzed by solid-phase microextraction coupled with gas chromatography–mass spectrometry (SPME–GC/MS), and among the detected compounds, 1-butanol, 3-methyl and 1-nonene resulted as the most produced. Their efficacy as pure synthetic compounds was assayed against mycelial growth of fungal pathogens by different concentrations (0.34, 0.56, and 1.12 µL mL−1 headspace). The effect of the application of VOCs as a biofumigant was also investigated as the expression level of seven defense-related genes of kiwifruit at different exposition times. The results indicated an enhancement of the expression of almost all the genes starting from 3 h of treatment. These results described P. synxantha VOCs characteristics and their potential as a promising method to adopt for protecting kiwifruit from postharvest diseases caused by C. luteo-olivacea and B. cinerea.